Commerce et connaissance du Nord : la marine française et la Baltique au XVIIIe siècle - Pourchasse, Pierrick (Presses universitaires de Rennes, 2019)
During the eighteenth century, French ships did not sail on the seas of Northern Europe. This absence of the merchant fleet in the North was a constant issue for French authorities. Sending French war ships to these regions was an easy way to acquire a lot of information on the Baltic Sea, to provide training opportunities and to enhance the interest of the North for the national merchant fleet. Between 1783 and 1786, five ships passed the Sound to load hemp in St. Petersburg and wood in Riga. These trips were also hydrographical campaigns organized to increase knowledge on northern maritime routes, and were also missions that provided excellent opportunities to collect political, diplomatic, economic and commercial intelligence and information.